ALOKASI WAKTU KERJA KELUARGA PENGRAJIN EMPING MELINJO DI KECAMATAN MLATI KABUPATEN SLEMAN (FAMILY TIME ALLOCATION FOR WORKING IN MELINJO CHIPS BUSSINES DISTRIBUTION AT MLATI SUB-REGENCY, SLEMAN REGENCY). - Nalinda, Rika (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
The study aimed to understand (1) time allocation of husband, wife and family members for working in melinjo chips business owned by its family (2) time allocation determinants for working in its business. Sample of this study are 39 families who run emping melinjo chips business in Mlati Sub-regency Sleman Regency. Data collected by interview methods. The results shows a different time allocation between male and female family worker by 1% degree of error. The wife allocate her time differently for working in its business and other businesses, statistically it is different significantly by 1% the degree of error. There is a significantly difference between husband's working-time allocation in melinjo chips business and others business The factors that influencing working-time allocation for wife are wife education, amount of melinjo chips production, amount of husband income and others businesses income. Factors that influencing the allocation of family members' working-time are: number of family worker and amount of melinjo chips production.